CLINICAL COURSE AND MODERN APPROACHES TO THE TREATMENT OF RHEUMATOID ARTHRITIS (Neo Scientific Peer Reviewed Journal, 2025)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune inflammatory disease characterized by progressive synovial inflammation, joint destruction, and a wide spectrum of extra-articular manifestations, leading to significant functional disability, reduced quality of life, and increased mortality if inadequately treated. Despite major advances in immunopathology and therapeutics, RA continues to pose substantial clinical and socioeconomic challenges due to its heterogeneous course, variable response to treatment, and frequent association with comorbid conditions. This scientific article aims to provide a comprehensive and up-to-date analysis of the clinical course and modern treatment strategies for rheumatoid arthritis, with an emphasis on early diagnosis, disease activity assessment, and evidence-based therapeutic interventions. Particular attention is given to the evolving treatment paradigm centered on early aggressive therapy, treat-to-target strategies, and the use of conventional synthetic, biologic, and targeted synthetic disease-modifying antirheumatic drugs. The article synthesizes current evidence from randomized controlled trials, meta-analyses, and international clinical guidelines, including recommendations from the European League Against Rheumatism and the American College of Rheumatology. Advances in understanding the immunological mechanisms underlying RA progression and their implications for personalized treatment approaches are critically discussed. This work is intended to serve as a scientific and practical reference for clinicians and researchers involved in the diagnosis and management of rheumatoid arthritis in contemporary clinical practice.